Intra-seasonal oscillations of convection over southern Africa - Levey, Kevin M (Department of Oceanography, 2014)
This work examines intra-seasonal rainfall variability over the summer rainfall region of South Africa. Spectral analysis of a precipitation minus evaporation index (P-E) compiled from 16 rainfall stations in the western Transvaal region of South Africa has shown that two dominant spectral peaks occur in the water budget or convection as identified by an outgoing longwave radiation (OLR) index and P-E index. A longer 40-60 day oscillation or Madden Julian Oscillation (MJO) and a shorter 20-30 day ISO are identified. The interaction between the Rossby waves of the mid-latitudes and the MJO of tropics appears to be the main cause of the 20-30 day ISO operating over southern Africa. Hovmoller analysis at 10° S and 40° S has shown that four modes exist in the propagation and oscillatory characteristics of various anomalies. Eastward and westward propagation is noted as well as standing wave patterns and "flip-flop" modes where anomalies alternate between positive and negative across the latitude band with time. The composite analysis revealed a tropically initiated signal of the 20-30 day ISO in the water vapour flux (WVF) anomaly field where strong easterly WVF vectors are noted between the equator and 10°S and between 40° E and 80° E. Strong convergence of water vapour occurs during the wet phase of the 20-30 day ISO over the south-western Indian Ocean and together with strong ridging of the South Atlantic Anticyclone (SAA) causes the south-easterly advection of moisture from the southern Mozambique Channel and over the warm Agulhas Current into South Africa. Post-wet phase anomaly composites do not show much similarity with pre-cursor anomaly composites. This implies that the 20-30 day ISO may be a half cycle of 40-60 days which is consistent with the MJO. However, it is felt that 20-30 day ISO's affecting the southern African region alternate in intensity within the period of the MJO.